Digital Social Security: Potential for Platform Work - Enzo Weber (Wirtschaftsdienst)
Abstract Social security in platform work has serious gaps. ‘Digital Social Security’ shows how social insurance can also be organised in a market with a very short-term and (partially) internationally integrated character. A digital mechanism is implemented in the platforms, which automatically pays a certain percentage of the agreed remuneration as a social contribution each time a job is finished. By integrating the DSS mechanism directly into the platform, an effective pay-as-you-go procedure for platform work is made possible. The system would be open to the participation of as many different states as possible. However, the national social security system remains fully sovereign and flexible.